2015
DOI: 10.1002/ajoc.201402207
|View full text |Cite
|
Sign up to set email alerts
|

Facile Dearomatization of Nitroquinolines through [3+2] and [4+2] Cycloaddition Reactions

Abstract: An efficient method was developed for the functionalization of nitroquinolines by employing pericyclic [3+2] and [4+2] cycloaddition reactions. The facile dearomatization of the nitrated benzene ring under the action of unstabilized N‐alkyl azomethine ylides and dienes led to fused heterocyclic systems. The 1,3‐dipoles smoothly and selectively underwent a cycloaddition reaction with the CC(NO2) fragment of the aromatic system if the position ortho to the nitro group was vacant, whereas the [4+2] cycloaddition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Recently, aromatic substrates (including heterocycles) have been reported to undergo [3+2]-cycloaddition by C=C bonds as dipolarophiles with azomethine ylides providing annulation of the pyrrolidine, pyrroline or pyrrole rings. [7][8][9][10] The present work extends our ongoing research [11][12][13][14][15][16] on the application of the dearomatization methodology to the synthesis of novel nitrogen-oxygen systems 17,18 -potential NO donors containing two or more pharmacophoric fragments. Since the 1980s, when the unique role of NO in the regulation of numerous physiological and pathophysiological processes was discovered, this small molecule has been of exceptional interest.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Recently, aromatic substrates (including heterocycles) have been reported to undergo [3+2]-cycloaddition by C=C bonds as dipolarophiles with azomethine ylides providing annulation of the pyrrolidine, pyrroline or pyrrole rings. [7][8][9][10] The present work extends our ongoing research [11][12][13][14][15][16] on the application of the dearomatization methodology to the synthesis of novel nitrogen-oxygen systems 17,18 -potential NO donors containing two or more pharmacophoric fragments. Since the 1980s, when the unique role of NO in the regulation of numerous physiological and pathophysiological processes was discovered, this small molecule has been of exceptional interest.…”
Section: Introductionsupporting
confidence: 55%
“…Earlier [26][27][28][29] we reported on the first example of [3+2]-cycloaddition of N-methyl azomethine ylide 1 to the benzene ring of a number of m-dinitro-benzohetarenes 2. This resulted in annulation of two pyrrolidine rings to the benzene ring and the formation of polycycles 3 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[27b] In a subsequent report, Bastrakov and co-workers demonstrated that 8-substituted 5,7-dinitroquinolines 98 were suitable reaction partners in 1,3-dipolar dearomative cycloaddition with unstabilized azomethine ylides (Scheme 18). [11,28] In the presence of substituted 5,7-dinitroquinolines and acyclic azomethine ylides, the corresponding isoindolines fused to a pyridine ring 99 were obtained, while the use of 8-arylamino-5,7-dinitroquinolines led to the formation of dearomative cycloaddition adducts 101. After the reaction of cyclic azomethine ylides with 8-substituted 5,7-dinitroquinolines, the initially formed dearomative cycloadducts (103') underwent a rearomatization to recover the aromaticity of the quinoline systems 102.…”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…The scope of 1,3‐DC with non‐stabilized azomethine ylides as electron‐rich dipole has been demonstrated and a high number of electron‐poor alkenes have been reported to react efficiently under these processes [28] . It has been also shown that electron‐deficient benzenes rings could behave as C=C dipolarophiles in spite of their inherent stability due to their aromatic character [29,30] . In this context, considering the lower aromaticity of the 2‐pyridone heterocycle, a higher reactivity of its C=C bonds as electron‐poor dipolarophiles can be expected.…”
Section: Introductionmentioning
confidence: 99%